Characterization of the intraday variability regime of solar irradiation of climatically distinct locations. (February 2016) - Lauret, Philippe; Perez, Richard; Mazorra Aguiar, Luis; Tapachès, Emeric; Diagne, Hadja Maimouna; David, Mathieu
Highlights: We propose a parameterization of the intraday variability regime. Three models are built to infer intraday variability from daily clear sky index. Sites influenced by local orography tend to exhibit more variability. Sites where cloud regimes are driven by weather tend to exhibit less variability. We propose an application of the model to improve day(s) ahead NWP forecasts. Abstract: This paper investigates the relationship between two parameters characterizing a given location on a given day: the daily clear sky index KT ∗ and the intraday variability given by the standard deviation of the changes in the hourly clear sky index σ ( Δ kt Δ t ∗ ) . Empirical evidence assembled from twenty climatically distinct locations led us to derive a simple model to infer intraday variability from the day's clear sky index. Although the model shows little dependence on location, we did observe a systematic difference traceable to a location's prevailing cloud formation regime. Therefore, we also propose two alternative models for sites where cloud formations is influenced by local orography and sites where cloud formation is traceable to weather events only. Finally, we present a possible application of the models to enhance the informative content of day(s) ahead NWP forecasts.